2015
DOI: 10.12911/22998993/1865
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF FOLIAR NUTRITION WITH InCa FERTILIZER ON THE CHEMICAL COMPOSITION OF LEAVES AND FRUITS OF SWEET CHERRY

Abstract: The aim of this study was to evaluate the effect of the foliar fertilizer InCa on the chemical composition of fruits and leaves of sweet cherry cultivar 'Burlat'. The study involved 14-year old sweet cherry trees of 'Burlat' cultivar, grafted onto 'PHL-A' rootstock and growing at 4×3 m spacing. The trees were sprayed with InCa calcium fertilizer based on CaT technology (manufacturer: Plant Impact). The fertilizer was applied three times, at a dose of 1.5 dm 3 •ha. The first foliar fertilization was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Use of the repellent did not influence the content of dry weight, nitrates, nitrites, macro and micronutrients, or heavy metals in the leaves and fruits of the 'Burlat' cultivar (Tables 1-3). The amount of mineral components determined in the leaves and fruits remained within the values provided in the literature [42][43][44][45][46].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Use of the repellent did not influence the content of dry weight, nitrates, nitrites, macro and micronutrients, or heavy metals in the leaves and fruits of the 'Burlat' cultivar (Tables 1-3). The amount of mineral components determined in the leaves and fruits remained within the values provided in the literature [42][43][44][45][46].…”
Section: Resultssupporting
confidence: 70%
“…When methyl anthranilate undergoes biodegradation, it loses its specific odor and does not affect the sensory parameters of fruits [22]. The content of dry weight and mineral components in the leaves and fruits of sweet cherry depends on a variety of factors, including cultivar, rootstock used, fertilization, foliar feeding, and irrigation [42][43][44][45]. Use of the repellent did not influence the content of dry weight, nitrates, nitrites, macro and micronutrients, or heavy metals in the leaves and fruits of the 'Burlat' cultivar (Tables 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Fertilizer products with CaT, such as InCaä (Miller Chemical) and similar experimental products reported in this article, are advertised to improve plant growth and fruit quality by reducing the negative effects of abiotic stresses, but there are few published reports about these products in the scientific literature. Sweet cherry (Prunus avium) trees treated with InCaä increased Ca concentration and dry matter in fruits and leaves relative to an untreated control; however, this experiment did not compare InCaä against CaCl 2 or other Ca products (Mikiciuk et al, 2015). In addition, there are several Agro-K (Minneapolis, MN) Ca products (i.e., Sysstem-Calä and Vigor-Calä), as well as the antitranspirant Vapor Gard Ò (Miller Chemical), which is thought to reduce transpiration rates and thus mitigate bitter pit development.…”
mentioning
confidence: 89%
“…Similarly, Ahmed et al (2014) reported that calcium chloride at 2% alone or in combination with other nutrients increase the calcium contents in leaves of pomegranate. Gregorz et al (2015) also reported that calcium spraying proved to be an effective way to deliver calcium to the plants, as it increases its content in both the leaves and the fruits of sweet cherry. Application of potassium sulphate might have led to increase in the potassium content of peel.…”
Section: Resultsmentioning
confidence: 99%